Removal of sulfanilic acid from wastewater by thermally activated persulfate process: oxidation performance and kinetic modeling. Issue 10 (18th July 2019) - Zhou, Rui; Li, Tingting; Su, Yu; Li, Chenguang; Jin, Xiong; Ren, Hejun
Abstract: BACKGROUND: Sulfanilic acid (SA) is a highly typical representative sulfonated aromatic amine widely occurring in chemical and pharmaceutical wastewaters. Its release poses potential threats to the environment and human health. Thermally activated persulfate (TAP) is a promising technology for organic matter removal. In this study, TAP is evaluated using the oxidation of SA as a model reaction. RESULTS: The oxidation performance of TAP on SA removal was investigated initially under different conditions of temperature, solution pH, persulfate dosage and initial SA concentration. Results showed that SA removal was effectively initiated by the TAP process and fitted well with a pseudo‐first‐order reaction model under all environmental conditions in water, and the yield of relatively low activation energy was 80.8 kJ mol −1 under the optimum conditions. The solution pH exerted almost no influence on SA removal. Sulfate radicals ( S O 4 − ) and hydroxyl radicals (HO ) were identified as major predominant free radicals by the electron paramagnetic resonance (EPR) spectrum and scavenger tests for removing SA during the TAP process. Non‐target natural water constituents can affect the removal rate of SA, such as the chloride ion (Cl − ) and the bicarbonate ion ( HCO 3 − ) promote whereas humic acid (HA) reduces the removal. The total organic carbon (TOC) monitoring results indicated that SA was almost completely mineralized into CO2 and H2 O during the 9 h reaction time. CONCLUSION: Owing to the generation of highly reactive oxidizing species ( S O 4 − and HO ), TAP oxidation as an environmentally friendly technology is a favorable option for SA‐containing wastewater treatment usage. © 2019 Society of Chemical Industry